Incorporating Diversity Into Animal Production Systems Can Increase Their Performance and Strengthen Their Resilience - Dumont, Bertrand; Puillet, Laurence; Martin, Guillaume; Savietto, Davi; Aubin, Joël; Ingrand, Stéphane; Niderkorn, Vincent; Steinmetz, Lucille; Thomas, Marielle (Frontiers in Sustainable Food Systems, 2020)
Animal production systems (APSs) have long been transformed through intensification, specialization and geographical concentration, leading them to become major anthropogenic drivers of pollution, climate change, and biodiversity loss. Agroecology, organic farming and sustainable intensification have been proposed as alternative models to invert those trends. Diversity is highly valued in agroecology and organic farming, in which it is assumed not only to increase farm performance but also to strengthen farm resilience. Here, we examine how the diversity of system components and interactions among these components can increase productivity, resource-use efficiency and farm resilience in aquaculture, rabbit, monogastric and ruminant systems. In doing so, we reveal that the same processes can occur in very different systems. For instance, the higher performance of multi-species aquaculture or ruminant grazing systems results from (i) the complementary feeding habits of animal species that exploit resources from different ecological niches more efficiently; and (ii) facilitation or competitive exclusion, which results in a species increasing or decreasing resource availability for another species. The benefits of diversity are observed not only in relatively extensive systems but also in intensive indoor systems. For instance, genetic diversity is associated with herd and social immunity in rabbit production, while trade-offs between life functions play a major role in dairy herd performance. In the last section, we discuss how management options nested in system component diversity and their interactions can enhance system resilience. Strategic and tactical management of APS diversity can promote farm buffering and adaptive capabilities, respectively, via the abovementioned processes. By stabilizing the farm financial situation and facilitating access to short supply channels, transformative changes, such as a diversification of the animal species bred or development of a processing enterprise on farm, expand options for increasing the resilience of APSs to market price fluctuations and climatic shocks. However, the need for new technical skills and sometimes high initial investments can act as strong inhibitors of farm diversification. We conclude with a description of some of the research or action that is needed for these principles to be more widely implemented in commercial farms.